2016
DOI: 10.1161/circimaging.116.005121
|View full text |Cite
|
Sign up to set email alerts
|

Outcome Implication of Aortic Valve Area Normalized to Body Size in Asymptomatic Aortic Stenosis

Abstract: Background— Current guidelines define severe aortic stenosis in patients with aortic valve area normalized to body surface area (AVA/BSA) <0.6 cm 2 /m 2 ; yet, this cutoff has never been validated. Moreover, it is not known whether AVA normalization to other body size indexes allows improved outcome prediction. We aim to test the value of AVA normalized to body size for outcome prediction in asymptomatic aortic stenosis. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(18 citation statements)
references
References 35 publications
2
16
0
Order By: Relevance
“…In clinical practice, assessment of the severity of AS in asymptomatic patients should not rely on a single parameter but on a multiparameter approach that combine data derived from flow indices as peak transaortic velocities (or gradients which are similar) with less flow-dependent indices as AVA and indexed AVA. 25 Global longitudinal strain is useful in risk-stratifying patients with AS 26,27 and could be a useful tool in the VSAS population. We can hypothesize that patients who are asymptomatic with Vmax ≥5 m/s could be further risk stratified on the basis of global longitudinal strain, thus providing clinicians with more robust tools to decide optimal timing of surgery in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…In clinical practice, assessment of the severity of AS in asymptomatic patients should not rely on a single parameter but on a multiparameter approach that combine data derived from flow indices as peak transaortic velocities (or gradients which are similar) with less flow-dependent indices as AVA and indexed AVA. 25 Global longitudinal strain is useful in risk-stratifying patients with AS 26,27 and could be a useful tool in the VSAS population. We can hypothesize that patients who are asymptomatic with Vmax ≥5 m/s could be further risk stratified on the basis of global longitudinal strain, thus providing clinicians with more robust tools to decide optimal timing of surgery in these patients.…”
Section: Discussionmentioning
confidence: 99%
“…Among all consecutive patients diagnosed with aortic stenosis, in the echocardiography laboratory of Saint Philibert Hospital (GHICL, Lille Catholic University, France) and included in a prospective registry[4], sixty-nine patients referred for exercise stress echocardiography of AS were retrospectively identified. Exclusion criteria were ( i ) left ventricular ejection fraction (LVEF) < 50%, ( ii ) more than mild-to-moderate concomitant aortic or mitral regurgitation.…”
Section: Methodsmentioning
confidence: 99%
“…As per current guidelines, severe AS is defined as the aortic valve area normalized to body surface area (AVA/BSA) < 0.6 cm 2 /m 2 . According to Tribouilloy et al[36], AVA/height showed better predictive performance than AVA/BSA withbetter reclassification and discrimination (net reclassification improvement, 0.33 vs. 0.28; integrated discrimination improvement, 0.10 vs. 0.08; C statistic, 0.67 vs. 0.65) than AVA/weight and AVA/body mass index. Inconsistency of hemodynamic characterization in severe AS between echocardiography (AVA < 1.0 cm 2 ) and catheterization (mean pressure gradient > 40 mm Hg) is observed in about half of the patients, and this is only partly explained by low-flow (low LV ejection fraction [EF]) conditions [37].…”
mentioning
confidence: 99%